The Authority Persecution in Shakir Khusbak’s theatrical texts - Ghazi Hussein Al-Sultani, Jamal (International Journal of Psychosocial Rehabilitation, 2020)
The centralization of the concept “authority persecution” as the idea of the individual who is able to control his various actions and express his thoughts and aspirations freely. This concept of “authority persecution” comes as a result of the individual's sense that he is restricted in all respects by the ruler or the person who is controlling him. So, through this study, the researcher tried to find out this concept in Shakir Khusbak's theatrical texts, whose texts formed a clear impact on the Iraqi theatrical text to this day.The researcher presented the basis for this study, which is entitled (The Authority Persecution in Shakir Khusbak’s theatrical texts), which consisted of four chapters, the first chapter of which was concerned with the methodological framework of the research containing the research problem in the following question (What is the Authority Persecution in Shakir Khusbak's theatrical texts)? The importance and need for this study were evident as it examined the manner in which the Iraqi playwright deals with his employment of dramatic treatment of the Persecution of the Authority, relying on scientific and literary facts and evidence.The goal of the research was to identify the persecution (oppression) of the authority in Shakir Khusbak's theatrical texts. As for the limits of the research, it was in time for the period from 1962 to 2007, and the place is in Iraq, which is the home of Shakir Khusbak. While objectively, it was a study of the persecution of authority in Shakir Khusbak's theatrical texts. This chapter was concluded by defining the necessary terms in the research title.As for the second chapter, it contains the theoretical framework and the indicators that resulted from this framework, including two topics. The first one deals with the study of the environmental and social reality of the writer Shakir Khusbak and his position about it.The third chapter included the procedural framework of the research, as the research community included (16) theatrical text by the author, which was determined by a theatrical text intended to suit the research community, taking into consideration the researcher’s temporal and spatial limits for the research. Explaining the reasons for choosing this sample. The research tool was the same indicators that the researcher extracted from his theoretical framework for research by analyzing the sample and using the analytical descriptive research method.As for the fourth chapter, the researcher presented his most important findings, which he reached after the analysis, building on them his recent conclusions in this chapter, and after that, his most important suggestions and recommendations for the research. Then, the researcher mentioned the research sources and references.